Paradigms for investigating invasive trophoblast cell development and contributions to uterine spiral artery remodeling. (15th September 2021) - Varberg, Kaela M.; Soares, Michael J.
Abstract: Uterine spiral arteries are extensively remodeled during placentation to ensure sufficient delivery of maternal blood to the developing fetus. Uterine spiral arterial remodeling is complex, as cells originating from both mother and developing conceptus interact at the maternal interface to regulate the extracellular matrix remodeling and vasculature restructuring necessary for successful placentation. Despite this complexity, one mechanism critical to spiral artery remodeling is trophoblast cell invasion into the maternal compartment. Invasive trophoblast cells include both interstitial and endovascular populations that exhibit spatiotemporal differences in uterine invasion, including proximity to uterine spiral arteries. Interstitial trophoblast cells invade the uterine parenchyma where they are interspersed among stromal cells. Endovascular trophoblast cells infiltrate uterine spiral arteries, replace endothelial cells, adopt a pseudo-endothelial cell phenotype, and engineer vessel remodeling. Impaired trophoblast cell invasion and, consequently, insufficient uterine spiral arterial remodeling can lead to the development of pregnancy disorders, such as preeclampsia, intrauterine growth restriction, and premature birth. This review provides insights into invasive trophoblast cells and their function during normal placentation as well as in settings of disease. Highlights: Uterine spiral arteries are restructured to ensure blood delivery to the fetus. Insufficient uterine spiral arterial remodeling can lead to pregnancy disorders. Maternal immune cells and trophoblast cells interact to regulate spiral artery remodeling. Invasive trophoblast cell lineage development is critical to uterine transformation.